Perilaku Pengobatan Sendiri yang Rasional pada Masyarakat - Susi Ari Kristina, Yayi Suryo Prabandari, Riswaka Sudjaswadi (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Self-medication is defined as used of drugs in community to relieve symptoms of minor illnesses without doctor  intervention. Self-medication have many advantages,  including safe  if properly used and relieve symptom of minor  illnesses  effectively. Self-medication  prevalence  in Indonesia  in  2005  is  24.1% and  in DIY province in 2004  is 87.73%. The behavior of rational self-medication is influenced by sex, age, education level, occupation,  income  level  , knowledge, and positive attitude  toward self-medication. The majority of community had  low level of self-medication knowledge,  therefore health promotion about self-medication  is very  important to be implemented in community.Method: This was  an observational  research with  cross sectional  design  that used quantitative method. The number of  respondent was 174, and  the samples were chosen by multistage  random sampling based on  the villages  number. Data was  collected by using  structured  questionnaire  and  nonpartisipative observation. The data was  analyzed  by  using  independent  sample  t-test, Pearson  correlation  and multivariate  analysis with multiple logistic regression.Result: The  result  of  the  research  showed  that  the majority   of  respondent’s  knowledge was  low  (52.9%), attitude was bad  (57.5%), and self-medication behavior was  irrational  (67.8%). The  result of bivariate analysis showed that there was significant relationship between sex, age, level of knowledge, occupation, income level, knowledge  and  attitude with  rational  self-medication  behavior. Resident  and  the  distance  from  health  facility were no significant related to rational self-medication behavior. Multivariate analysis result showed that education level was  the most  influencing  rational self-medication behavior at confidence  level 95%.Conclusion: There was  significant  relationship  between  knowledge  and attitude with  rational  self-medication behavior. Sociodemographic  factors  that  have  significant  relationship with  rational  self-medication  behavior were  sex,  age,  level  of  knowledge,  occupation  and  income  level. Education  level was  the most  influencing rational self-medication behavior.Keywords:  self-medication  behavior,  knowledge,  attitude,  sociodemographic  factors